2021
DOI: 10.1093/ijnp/pyab015
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Association of Cigarette Craving With Insula Structure

Abstract: Background Cigarette craving, which can negatively impact smoking cessation, is reportedly stronger in women than in men when they initiate abstinence from smoking. Identifying approaches to counteract craving in people of different sexes may facilitate the development of personalized treatments for Tobacco Use Disorder, which disproportionally affects women. Because cigarette craving is associated nicotine dependence and structure of the insula, this study addressed whether a person’s sex in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…The study was part of a larger investigation on the brain correlates of smoking behavior and took place between September, 2017 and February, 2020. Another report from that study is in press 52 . The study was conducted at the Semel Institute for Neuroscience and Human Behavior at the University of California, Los Angeles (UCLA).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The study was part of a larger investigation on the brain correlates of smoking behavior and took place between September, 2017 and February, 2020. Another report from that study is in press 52 . The study was conducted at the Semel Institute for Neuroscience and Human Behavior at the University of California, Los Angeles (UCLA).…”
Section: Methodsmentioning
confidence: 94%
“…Neuroimaging studies have also indicated the importance of the insula in maintenance of cigarette smoking. Cortical thickness of insular sub-regions is negatively related to nicotine dependence 1719 and cigarette craving 20 . Resting-state functional connectivity (RSFC) has been used to assess neural systems involved in nicotine dependence 21, 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The current observation that insular thickness is negatively associated with craving is line with previous research in cigarette smokers. 30 , 31 Thinner insular cortex 54 , 55 , 56 and smaller insular volume 25 , 56 , 57 has furthermore been associated with heightened impulsive and compulsive behaviour. Hence, insular thinning may be a biomarker for impaired emotion regulation and, as a consequence, enhanced craving.…”
Section: Discussionmentioning
confidence: 99%
“…Although we expected these sex differences to be particularly pronounced in insular CT, these findings are in line with previous research that demonstrated that abstinence induced craving is negatively related to insular CT in nicotine dependent women, but positively related to insular CT in nicotine dependent men. 31 Lower insular volume, which is the product of insular thinning and reductions in surface area, has shown to be related to impaired attentional control in cocaine users. 25 In addition, we also found that craving related to loss of control and right insular SA was also moderated by sex: There was a positive association between right insular SA and craving related to loss of control in CU women, whereas this association was negative in CU men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation